Penggunaan Safranin sebagai Pewarna Alternatif dalam Pengamatan Mikroskopik Daun Bayam - Amelia Putri Az Zahra; Azlinatul Lulu Kharolaini; Feni Atika Tsuroya; Khotimah Nur Ramadhani; Pramai Sheila eka khoireina; Septi Puspita Kurniawati; Liss Dyah Dewi Arini (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Microscopic staining is an important technique in observing plant tissue to increase contrast and clarify cellular structures. One of the dyes commonly used in plant tissue studies is Safranin, a cationic base compound from the azo group that has a high affinity for cell components that produce negative impacts such as lignin and nucleic acids. This study aims to determine the effectiveness of Safranin as an alternative dye in microscopic observation of spinach leaf tissue (Amaranthus spp.). The practicum was carried out using the wet preparation method, using cross-sections of spinach leaves stained with Safranin solution, then observed under a light microscope. The results showed that Safranin was able to provide good red color contrast to cell walls, cell nuclei, and blood vessel tissue, so that structures such as epidermis, palisade tissue, sponges, and xylem and phloem could be clearly identified. However, obstacles arise in the regulation of concentration and duration of staining, where excess of both can cause excess and excessive structural accuracy. Therefore, adjustment of technical parameters is needed to obtain optimal results. These findings indicate that Safranin is effective as a microscopic dye and has the potential to be used in educational practicum activities, because it is economical, safe, and easy to apply. This study also applies the interdisciplinary application of chemistry and biology in science learning.